Perceived stress, resilience, self-esteem as predictors of life satisfaction among university students in Malaysia - Chueh, Di-An; Hen, Cavin; Lim, Ya Xuan (2023)
Life satisfaction of university students has been discovered to be significantly linked with mental health issues such as anxiety, stress, and depression. To ascertain the predictive impacts of perceived stress, resilience, and self-esteem on life satisfaction among Malaysian university students, a quantitative and cross-sectional study was carried out. The Sociometer Theory and the Stress and Coping Theories served as the study's theoretical foundation. With the use of the purposive and snowball sampling techniques, 99 respondents were found. An online questionnaire was distributed to the participants through MS Team, Messenger, WhatsApp, and so on. The participants were students enrolled in Malaysian public or private institutions, ranging from the age of 19 to 24 years old (M = 21.46). There were 42.4% of male participants (n = 42) and 57.6% of female respondents (n = 57). The Perceived Stress Scale (PSS), Brief Resilience Scale (BRS), Rosenberg Self-Esteem Scale (RSES), and Satisfaction with Life Scale were the tools employed in this study (SWLS). The findings discovered that only self-esteem was significant and positively predict life satisfaction, while perceived stress and resilience were not a significant predictor to life satisfaction among Malaysian university students. Therefore, this study may offer a more in-depth insight into pertinent topics and play a part as useful pointers for future researchers. All the information within this study could also provide significant knowledge for responsible authorities to come out with effective strategies in booting the life satisfaction among university students in Malaysia.